Pengembangan Fasilitas Penunjang Untuk Mendukung Perkembangan Pariwisata Di Desa Belumbang Tabanan - Kardana, I Ketut (Universitas Triatma Mulya, 2025)
The development of tourism in rural areas requires adequate supporting facilities to ensure visitor comfort, safety, and satisfaction. Belumbang Village, located in Tabanan Regency, has significant tourism potential based on its natural landscapes, cultural attractions, and local community activities. However, the limited availability and quality of supporting facilities such as access roads, sanitation, signage, resting areas, and basic tourism infrastructure have become obstacles to the optimal growth of tourism in the village. This study aims to analyze the development of supporting facilities needed to enhance tourism growth in Belumbang Village. A qualitative descriptive approach was applied through field observations, interviews with local stakeholders, and documentation studies. The findings indicate that improving supporting facilities plays a crucial role in increasing tourist accessibility, improving visitor experience, and strengthening community participation in tourism development. The study highlights the importance of integrated facility planning that aligns with local potential, environmental sustainability, and community-based tourism principles. The results are expected to provide practical recommendations for local governments and village stakeholders in developing sustainable tourism facilities that contribute to the long-term tourism growth of Belumbang Village.